Fifty years of panchayati raj and decentralised development - Hooja, Rakesh (ed.); Dutt, Sunil ( ed.) (New Delhi, 2010)
The present volume captures the journey of Panchayati Raj from an institution within the culture of India to organs of decentralised governance with constitutional status.
Keywords: Panchayati raj